2011
DOI: 10.1038/nrrheum.2011.61
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin therapy in rheumatic diseases

Abstract: Prepared from the collective plasma of several thousand people, therapeutic intravenous immunoglobulin (IVIg) consists mostly of human polyspecific IgG. In addition to its use in primary and secondary immune deficiencies, IVIg is used in the treatment of several rheumatic conditions, including Kawasaki disease, dermatomyositis and antineutrophil cytoplasmic antibody (ANCA)-positive vasculitis. In these diseases, IVIg therapy generally involves the use of 2 g/kg administered over either 2 or 5 consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
87
0
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(92 citation statements)
references
References 115 publications
0
87
0
5
Order By: Relevance
“…Although efficacious in these diseases, the precise mechanism of action of IVIg is not well-understood. Various studies have documented a series of nonmutually exclusive mechanisms modulating components of the innate and adaptive immune system (4,6). For example, IVIg has been shown to mediate anti-inflammatory responses through its action on dendritic cells, natural killer cells, regulatory T cells, B cells, and the monocyte/macrophage system, and through its suppression or neutralization of soluble factors, such as inflammatory cytokines, chemokines, and pathogenic autoantibodies (5)(6)(7).…”
mentioning
confidence: 99%
“…Although efficacious in these diseases, the precise mechanism of action of IVIg is not well-understood. Various studies have documented a series of nonmutually exclusive mechanisms modulating components of the innate and adaptive immune system (4,6). For example, IVIg has been shown to mediate anti-inflammatory responses through its action on dendritic cells, natural killer cells, regulatory T cells, B cells, and the monocyte/macrophage system, and through its suppression or neutralization of soluble factors, such as inflammatory cytokines, chemokines, and pathogenic autoantibodies (5)(6)(7).…”
mentioning
confidence: 99%
“…Currently, high-dose IVIg therapy (1-2 g/kg body weight) is used in the treatment of diverse autoimmune and inflammatory conditions, such as Guillain-Barré syndrome (GBS), Kawasaki disease, idiopathic thrombocytopenic purpura and inflammatory myositis. 1 The beneficial effects of IVIg are mediated by numerous mutually non-exclusive cellular and molecular mechanisms. These mechanisms indirectly suggest the functions of circulating IgG in the maintenance of immune homeostasis.…”
mentioning
confidence: 99%
“…However, a recent study suggested that Efungumab potentiation of amphotericin B could be non-specific [108]. Although a status of an orphan drug has been given in USA for this antibody, Initially used for the replacement therapy of primary and secondary immunodeficiencies, high-dose (1-2 g/kg body weight) IVIg is currently used in the therapy of diverse autoimmune and inflammatory diseases such as Kawasaki disease, Guillain-Barré Syndrome, inflammatory myopathies, immune thrombocytopenic purpura, chronic inflammatory demyelinating polyneuropathy, vasculitis, graft versus host disease, and others as an immunomodulatory agent with no reports of serious side effects [110][111][112][113][114][115]. In addition to invasive disease, fungi species are also associated with several inflammatory conditions such as both IgE and eosinophiliadriven hypersensitivity diseases including severe asthma, allergic bronchopulmonary mycoses, chronic sinusitis, hypersensitivity pneumonitis, atopic eczema/dermatitis syndrome and gut inflammation.…”
Section: Role Of Antibodies In the Protection Against Fungal Infectiomentioning
confidence: 99%